Implicações federativas da emenda Ibsen Pinheiro - Lemos, Fernando Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Since it was proposed, the Ibsen Pinheiro amendment has given rise to a huge debate in Brazilian society. This amendment proposes to share the revenue generated by royalties and special participations from offshore oil drilling between all municipalities and states, using for this the states and municipalities participation funds. This new distribution is a great rupture with the current model, which mandates that these resources should only be distributed to producing municipalities and states. Since the new proposal affects all offshore operations, and not only those in the new pre-salt areas, the producing municipalities and states would face an immediate loss of revenue in the scale of billions of reais. This study's objective is to analyze the validity of the criteria of redistribution of the government participations proposed by the Ibsen amendment. In this sense, we present the current Brazilian government participation model, focusing on the overfinancing of subnational spheres generated by this model, and compare it to a distribution simulation using the Ibsen amendment criteria. This comparison shows that the current beneficiaries would face a significant loss of revenue, and a distribution that favors the poorest regions of the country, consequence of the states and municipalities participation funds use. The study's last part discusses the various arguments in favor and against the amendment, especially those of constitutional character, most of which are contrary to the Ibsen amendment

Desde que foi proposta, a emenda Ibsen Pinheiro vem suscitando enorme debate na sociedade brasileira. Esta emenda propõe dividir os recursos provenientes dos royalties e participações especiais da exploração offshore entre todos os municípios e estados, utilizando-se para tal os fundos de participações dos estados e dos municípios. Esta nova divisão é uma grande ruptura com o modelo vigente, que determina a distribuição destes recursos somente entre os municípios e estados produtores. Como a nova proposta afeta todas as operações offshore, e não somente as novas áreas do pré-sal, haveria uma perda imediata de receita dos municípios e estados produtores da ordem de bilhões de reais. O presente estudo tem como objetivo analisar a validade dos critérios da redistribuição das participações governamentais proposta pela emenda Ibsen. Nesta direção, apresentamos o modelo vigente de distribuição de participações governamentais no Brasil, focando o sobrefinanciamento das esferas subnacionais gerado por este modelo, e o comparamos a uma simulação de distribuição de acordo com os critérios da emenda Ibsen. Esta comparação mostrou que haveria uma perda significativa de renda por parte da maioria dos atuais beneficiários e um rateio que privilegia as regiões mais pobres do país, fruto da utilização dos critérios dos fundos de participação dos municípios e dos estados. A última parte do estudo trabalha os diversos argumentos pró e contra a emenda, em especial os de caráter constitucional, em grande parte contrários a emenda Ibsen
Keywords: Pinheiro, Ibsen; Economia; Direitos autorais - Royalties; Pré-sal; Petróleo; Oil